Local Wisdom in the Sustainable Conservation of Durian Gardens in Benawai Agung Village, Kayong Utara Regency - Ilyas Maulana Akbar (Jurnal Agroteknologi dan Inovasi Pertanian, 2025)
The Durian orchards are one form of land management by the community with an agroforestry system in Benawai Agung village, which still survives to this day. This study aims to explain the variety of durian fruit preserved by the community and explain the local wisdom of the community in preserving the preservation of the Durian Orchard in Benawai Agung Village. The method used in this study is a survey method with interview techniques, with the help of a questionnaire. Respondents were taken by purposive sampling, with a total of 88 respondents. The data analysis used is qualitative descriptive analysis. There are 11 types of durian fruit variations in the durian orchard, namely the kelentet nyamok durian, the long sparse hair durian, the jabrik junai durian, the jabrik junai durian, the sleeping cat durian, the sigenta durian, the broken tempoyak durian, the sipipit durian, the sicanggai durian, the landang batang durian, the black thorn durian, and the sikuning durian. The management of the existing durian orchard is a legacy that has been passed down until now and is a source of income for the community. In managing the orchards, the community is bound by prevailing cultural and cultural norms, such as prohibitions on burning and cutting down productive durian trees, and prohibitions on littering within the orchards. The community's mutual cooperation in cleaning the orchards every harvest season, along with the regulations governing durian orchard management, has ensured the sustainability of the orchards in Benawai Agung Village..